Institutionalizing Non-institutionalization: Toward Sustainable Commoning - Smets, Peer; Volont, Louis (Frontiers in Sustainable Cities, 2022)
The goal of this article is to revive and empirically expand the debate on institutional frameworks within commons scholarship. The paper's guiding question is: what kind of institutional framework allows for sustainable commoning in urban conditions? In order to answer this question, we invoke the case of Savings and Credit Associations, a form of financial commoning whereby participants lend each other money and decide, through deliberative sessions, how the money is to be shared. We mobilize data from three decades of ethnographic research in India and The Netherlands, in order to distill the institutional properties that have contributed to Savings and Credit Associations' sustainable existence. The paper's main claim will be that in Savings and Credit Associations' institutional frameworks, a pivotal precondition for sustainable commoning can be found: the combination of a socio-relational (low-scale, trust-based) approach with a reconsideration of the rules at given intervals. In conclusion, we also argue that it's precisely a socio-relational approach which may save commoning's emancipatory potential.